Geophysics for Mineral Exploration - Zhdanov, Michael S. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue contains ten papers which focus on emerging geophysical techniques for mineral exploration, novel modeling, and interpretation methods, including joint inversions of multi physics data, and challenging case studies. The papers cover a wide range of mineral deposits, including banded iron formations, epithermal gold-silver-copper-iron-molybdenum deposits, iron-oxide-copper-gold deposits, and prospecting forgroundwater resources.